Contact lens compliance among contact lens wearer in UiTM Puncak Alam / Nurul Syafiqa Abdul Hadi - Abdul Hadi, Nurul Syafiqa (2016)
Background: Many contact lens wearers did not get proper guidance on contact lens wear and care resulting in non compliance behavior. The non compliance behavior is associated with increasing risk of contact lens compliancation such as microbial keratitis and fusarium keratitis Aim: The aim of this study was to evaluate the level of compliance and the scope of noncompliance behavior among contact lens wearers in UiTM Puncak Alam. Method: A total of 66 soft contact lens wearers were selected conveniently in the university campus. After getting the consent form, a set of self report questionnaire consisted of demographic background, contact lens details, perceived compliance and assessment on wearing and replacement habits and care of lens accessories were administered. Then, each participants was asked to demonstrate the lens cleaning and disinfecting procedure according to their normal practices rather that they thought they should demonstrated. The observational checklist was used by the researcher for the assessment. Results: Majority of participants was female (n=61) aged between 20-25 years old. Of 66 participants, only 47.8% were identified to be compliant to the lens wear and care regiment. The most noncompliant behavior was the lens cleaning and disinfecting procedure (59.1%) followed by care of lens case accessories (48.5%). It was found that 56 participants failed to come for aftercare assessment and that was significantly associated with the location of their contact lens purchase (p=0.04). Of 34.8% of participants who perceived themselves as good contact lens wearer, only half (n=12) exhibited as good contact lens wearer. Conclusion: This study demonstrates that the level of compliance among young contact lens wearer was still low. The area of contact lens cleaning and disinfecting is the most noncompliance behavior demonstrated by the participants and this may be attributed by lack of proper knowledge on lens wear and care.